Application of Gamification in Digital Library Systems Based on MDA Framework - Siti Aminah; Faris Purnomo; Hilman Nuril Hadi (Teknika, 2026)
The digital library of Bhinneka Nusantara University has experienced low user engagement, with an average of only 166 visits per month as of June 2025. This study aims to design and evaluate a gamified digital library system to address this issue. The system integrates key gamification elements points, leaderboards, and challenges and badges based on the Mechanics and Aesthetics components of the Mechanics–Dynamics–Aesthetics (MDA) Framework. The system was developed using the System Development Life Cycle (SDLC), encompassing needs analysis, system design, gamification implementation, and testing. Functional testing and User Experience (UX) evaluation were conducted to assess the effectiveness of the system. The results show that the gamified features have a positive impact on user perception, satisfaction, motivation, and pleasure.